Frontline Science: Aspirin-triggered resolvin D1 controls herpes simplex virus-induced corneal immunopathology. Issue 5 (1st November 2017) - Rajasagi, Naveen K; Bhela, Siddheshvar; Varanasi, Siva Karthik; Rouse, Barry T
Abstract : AT-RvD1 plays a role in controlling herpes stromal keratitis lesions. Abstract: Stromal keratitis (SK) is a chronic immunopathological lesion of the eye, caused by HSV-1 infection, and a common cause of vision impairment in humans. The inflammatory lesions in the cornea are primarily caused by neutrophils with the active participation of CD4 + T cells. Therefore, the targeting of these immune cell types and their products represents a potentially valuable form of therapy to reduce the severity of disease. Resolvin D1 (RvD1) and its epimer aspirin-triggered RvD1 (AT-RvD1) are lipid mediators derived from docosahexaenoic acid (DHA) and were shown to promote resolution in several inflammatory disease models. In this report, we examined whether AT-RvD1 administration, begun before infection or at a later stage after ocular infection of mice with HSV-1, could control the severity of SK lesions. Treatment with AT-RvD1 significantly diminished the extent of corneal neovascularization and the severity of SK lesions. AT-RvD1-treated mice had fewer numbers of inflammatory cells that included neutrophils as well as Th1 and Th17 cells in the infected cornea. The mechanisms by which AT-RvD1 acts appear to be multiple. These include inhibitory effects on proinflammatory mediators, such as IL-1β, IL-6, IL-12, CXCL1, MCP-1, MIP-2, vascular endothelial growth factor (VEGF)-A, matrix metalloproteinase 9 (MMP-9), and proinflammatory miRNA, such as miR-155, miR-132, and miR-223, which are involved in SK pathogenesis and corneal neovascularization. In addition, AT-RvD1 attenuated STAT1, which plays an important role in Th1 cell differentiation and IFN-γ expression. These findings demonstrate that AT-RvD1 treatment could represent a useful strategy for the management of virus-induced immunopathological lesions.